1994
DOI: 10.1161/01.res.74.6.1141
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates NADH and NADPH oxidase activity in cultured vascular smooth muscle cells.

Abstract: The signaling pathways involved in the long-term metabolic effects of angiotensin II (Ang II) in vascular smooth muscle cells are incompletely understood but include the generation of molecules likely to affect oxidase activity. We examined the ability of Ang II to stimulate superoxide anion formation and investigated the identity of the oxidases responsible for its production. Treatment of vascular smooth muscle cells with Ang II for 4 to 6 hours caused a 2.7 +/- 0.4-fold increase in intracellular superoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
1,820
9
41

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,452 publications
(1,936 citation statements)
references
References 48 publications
50
1,820
9
41
Order By: Relevance
“…4 Angiotensin II stimulates the production of free radicals within the endothelial monolayer with subsequent increase of oxidative stress and development of endothelial dysfunction. 5,6 Moreover, local angiotensin II, synthesized in cavernosal tissue exerts direct effects on erectile function, as indicated by the termination of spontaneous erection by intracavernosal injection of angiotensin II. 7 Thus, inhibition of the renin-angiotensin system (RAS) may improve erectile function by inhibition of specific effects of angiotensin II in the corpus cavernosum, reduction of blood pressure and amelioration of endothelial function in the corpus cavernosum and the penile arteries.…”
Section: Introductionmentioning
confidence: 99%
“…4 Angiotensin II stimulates the production of free radicals within the endothelial monolayer with subsequent increase of oxidative stress and development of endothelial dysfunction. 5,6 Moreover, local angiotensin II, synthesized in cavernosal tissue exerts direct effects on erectile function, as indicated by the termination of spontaneous erection by intracavernosal injection of angiotensin II. 7 Thus, inhibition of the renin-angiotensin system (RAS) may improve erectile function by inhibition of specific effects of angiotensin II in the corpus cavernosum, reduction of blood pressure and amelioration of endothelial function in the corpus cavernosum and the penile arteries.…”
Section: Introductionmentioning
confidence: 99%
“…In response to angiotensin II, enzymes in the endothelium, smooth muscle, and fibroblasts that use nicotinamide adenine dinucleotide (NADH), nicotinamide adenine dinucleotide phosphate (NADPH) substrates, or both, are activated and yield superoxide anion. [16][17][18][19][20] Therefore, we would expect superoxide production to increase when the local or systemic renin-angiotensin system (RAS) is activated-and increased vascular NADH/NADPH oxidase activity has been demonstrated in animal models of early atherosclerosis along with activation of the RAS. 21 When NADH/NADPH oxidase is activated, the amount of superoxide within the vascular wall increases, and atherosclerosis can progress.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Specifically, several proinflammatory cytokines and growth factors (tumor necrosis factor-alpha [TNF-␣], interleukin-1␀ [IL-1␀], and interferon-gamma [IFN-␄]) as well as angiotensin II activate membrane-bound NADPH-like oxidase activity in endothelial and vascular smooth muscle cells, resulting in superoxide anion production. 16,17,19,21 Superoxide and other free radicals promote LDL oxidation and degradation of NO. The ROS that are responsible for LDL oxidation also stimulate the synthesis of other vascular inflammatory products and adhesion molecules that include monocyte chemoattractant protein-1 (MCP-1), vascular cell adhesion molecule-1 (VCAM-1), and intercellular adhesion molecule-1 (ICAM-1).…”
Section: The Role Of Angiotensin-converting Enzyme Inhibition and Angmentioning
confidence: 99%
“…It is well known that angiotensin II stimulates the NADH/NAD(P)H oxidase of endothelial and smooth muscle cells. 25 Figure 1 shows the effects of highly specific tissular ACE inhibitors in restoring the balance on the endothelial production of NO and O − 2 . Recent evidence has shown that acute administration of calcium antagonists improves the abnormal coronary vasomotion response in hypertension, atherosclerosis and hypercholesterolaemia.…”
Section: Angiotensin-converting Enzyme (Ace) Inhibitors and Calcium Amentioning
confidence: 99%